Relation of JAK2 V617F allele burden and coronary calcium score in patients with essential thrombocythemia - Drofenik Ajda; Blinc Ales; Bozic Mijovski Mojca; Pajic Tadej; Vrtovec Matjaz; Sever Matjaz (Radiology and Oncology)
JAK2 V617F (JAK2) mutation is associated with clonal hemopoiesis in myeloproliferative neoplasms as well as with faster progression of cardiovascular diseases. Little is known about the relationship between allele burden and the degree of atherosclerotic alteration of coronary vasculature. We previously reported that carotid artery stiffness progressed faster in patients with JAK2 positive essential thromocythemia (ET) patients. After a four-year follow-up we investigated whether mutation burden of a JAK2 allele correlates with a higher coronary calcium score.